Efficiency of Betacyanin and Betaxanthin Extraction from Red Beets (Beta vulgaris L.) using Microwave-Assisted Extraction (MAE) - Pramudika, Satya; Paramita, Vita (Vocational College of Universitas Diponegoro, 2023)
Red beet pigments, betacyanin and betaxanthin, possess both health benefits and potential as natural colorants. This study investigated the efficacy of Microwave-Assisted Extraction (MAE) for their extraction from red beets. Pretreated beets were subjected to MAE employing varying microwave power levels (200, 400, and 600 W) and solvents (water, ethanol, and ethanol + citric acid). Betacyanin content varied from 23.77 to 59.28 mg/100g. Higher microwave power significantly increased betacyanin yield (p < 0.05), while the type of solvent did not exert a significant influence. Betaxanthin content was also affected by both microwave power and solvent polarity. Higher power settings and the more polar solvent mixture (ethanol + citric acid) resulted in greater extraction. These findings demonstrate the effectiveness of MAE for extracting both pigments from red beets, with optimal conditions dependent on the target compound of interest.